Comparison of early results of vascularized and non-vascularized fibular grafting in the treatment of osteonecrosis of the femoral head - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2011)
Objective: Osteonecrosis of the femoral head, a disease primarily affecting young adults, is often associated with the collapse of the articular surface and subsequent arthrosis. Some authors have reported good results with the use of vascularized and non-vascularized fibular grafts to treat osteonecrotic lesions of the femoral head. The aim of this study was to compare the results of vascularized fibular grafting with that of non-vascularized fibular grafting in the treatment of femoral head osteonecrosis. Methods: Between January 1999 and June 2008, 11 osteonecrotic hips of 8 patients who underwent vascularized fibular grafting and 15 osteonecrotic hips of 13 patients who underwent non-vascularized fibular grafting were compared according to etiology, stage, age, sex, preoperative and postoperative first year Harris hip and VAS scores. Results: Steroid use was the most common etiologic factor, found in 26 hips of 21 patients in the entire patient population. There was no significant difference between the two groups according to their age, sex and preoperative Harris hip scores (p>0.05). According to the Ficat staging system for radiological evaluation, 4 hips were Grade 2A, 4 hips were Grade 2B, and 3 hips were Grade 3 in the vascularized group and 8 hips were Grade 2A, 3 hips Grade 2B, 3 hips Grade 3 and one hip was identified as Grade 4 in the non-vascularized group. When the Harris hip and VAS scores of both groups were evaluated, the group treated by vascularized fibular grafting had significantly higher scores than the ones treated by non-vascularized fibular grafting in the other group (p<0.05). Furthermore, when the Harris hip and VAS scores of preoperative and postoperative first year of vascularized fibular grafting patients were compared, there were significantly higher scores after the surgery. Conclusion: Although there was no significant radiological difference in the early results of both surgical techniques, the clinical results of vascularized fibular grafting treatment were significantly better than the results of non-vascularized fibular grafting treatment in the osteonecrosis of the femoral head. Vascularized fibular grafting improves the clinical status at an early period and prevents subchondral collapse.
Keywords: Femur head osteonecrosis; fibular grafting; Ficat staging; vascularized fibular grafting; NONTRAUMATIC AVASCULAR NECROSIS; CORE DECOMPRESSION; ASEPTIC NECROSIS; NATURAL-HISTORY; HIPS; OSTEOTOMY